THE INFLUENCE OF MOTIVATION, LEARNING DISCIPLINE, TEACHER COMPETENCE AND PARENTAL SUPPORT ON ACADEMIC ACHIEVEMENT OF STUDENTS (STUDY ON GAMA ENGLISH COURSE SUKOHARJO) - Fitri Ainurrohmah; Rini Handayani (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
Student achievement is very important to improve the quality of human resources. Each student's academic performance is different even in the same situation. Many factors influence students in their academic achievement. Academic achievement is a result achieved by students in the learning process at a certain time. This study aims to determine the effect of motivation, learning discipline, teacher competence and parental support on student academic achievement. This research used quantitative descriptive with a sample of 90 students of the Gama English Course Sukoharjo. The sampling technique used was survey sampling with data collection using a questionnaire. The data analysis technique used multiple linear regression analysis and was processed with SPSS 23. The determinant coefficient of the research results showed that motivation, learning discipline, teacher competence and parental support could explain the student's academic achievement by 62.3%. The results of the study concluded that there was a positive effect of teacher motivation and competence on student academic achievement, but learning discipline and parental support had a negative effect on student academic achievement.